Literary Characteristics of High Middle Ages Germany in Die Nibelungen: Siegfried (1966) Film and Its Relevance to Learning in Literaturgescichte Course - Aura Reandra Paramitha; Herri Akhmad Bukhori (Universitas Negeri Malang, 2022)
The purposes of this study were to describe the literary characteristics of German Literature in High Middle Ages, the literary charactersistics through Die Nibelungen: Siegfried film and the relevance between the identified literary characteristics in the film and the learning in Literaturgeschichte course. The data sources of this study were Die Nibelungen: Siegfried film and various literatures. The datas were the literary characteristics from the film scenes and descriptions to elaborate the analysis further. Datas were acquired through documentation method and analyzed through content analysis. The results of this study indicated that the literary characteristics of German Literature in High Middle Ages are the emphasis in chivalrous acts and matters of courtly love in the literatures. A few scenes from the film also contained the two main literary characteristics. There were relevancies between research datas and learning in Literaturgeschichte course based on the CLO and topics found in the RPS. Keywords: literary characteristics, Hochmittelalter, Literaturgeschichte